2018
DOI: 10.4049/jimmunol.1700544
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophages Drive Hepatocellular Carcinoma Lung Metastasis by Generating Leukotriene B4

Abstract: Macrophages in lungs can be classified into two subpopulations, alveolar macrophages (AMs) and interstitial macrophages (IMs), which reside in the alveolar and interstitial spaces, respectively. Accumulating evidence indicates the involvement of IMs in lung metastasis, but the roles of AMs in lung metastasis still remain elusive. An i.v. injection of a mouse hepatocellular carcinoma (HCC) cell line, BNL, caused lung metastasis foci with infiltration of AMs and IMs. Comprehensive determination of arachidonic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 54 publications
0
37
1
Order By: Relevance
“…The lung microenvironment comprises airway, AM, and IM, as well as inflammatory and patrolling monocytes. Previous studies have shown that patrolling monocytes can control tumor metastasis to the lungs (28), whereas AM contribute to the promotion of lung metastasis by suppressing Th1 response (30,42). However, we did not observe the causal relationship of AM in the experimental LLC lung metastasis model.…”
Section: Discussioncontrasting
confidence: 87%
“…The lung microenvironment comprises airway, AM, and IM, as well as inflammatory and patrolling monocytes. Previous studies have shown that patrolling monocytes can control tumor metastasis to the lungs (28), whereas AM contribute to the promotion of lung metastasis by suppressing Th1 response (30,42). However, we did not observe the causal relationship of AM in the experimental LLC lung metastasis model.…”
Section: Discussioncontrasting
confidence: 87%
“…These observations would indicate that bone marrow contains AM precursors, which can migrate through circulating blood into lung to differentiate into mature AMs. Likewise, we observed in a mouse lung metastasis model that blood-derived AM precursors can infiltrate into lungs to differentiate into AMs [39], as discussed in the following section. However, it remains elusive on the precise phenotypes of AM precursors in bone marrow and circulating blood.…”
Section: Monocytes and Tissue-resident Macrophages In The Normal Lmentioning
confidence: 93%
“…We recently observed that an intravenous injection of mouse hepatocellular carcinoma cells caused lung metastasis, together with increases in both F4/80 + CD11b − CD11c + AMs and F4/80 + CD11b + CD11c − IMs [39]. Intratracheal injection of CLL transiently reduced AMs but not IMs, and attenuated lung metastasis upon its administration at a later step when tumor cells had already seeded into lungs.…”
Section: Monocytes and Macrophages In The Lung With Metastatic Tummentioning
confidence: 99%
See 1 more Smart Citation
“…AMΦ and other innate immune cells can also prepare the lungs for metastatic seeding through means of immune stimulation. In mouse models of hepatocellular carcinoma, AMΦ‐derived leukotriene B 4 has been shown to increase metastatic permissiveness of the lungs, such that inhibition of the leukotriene‐generating enzyme, 5‐lipoxygenase (Alox5), is sufficient to prevent pulmonary colonization (Figure A). Neutrophils also contribute to Alox5 production in breast cancer models, which facilitates the production of leukotrienes , suggesting that these mechanisms may be more universally applicable to lung metastases from multiple primary sources.…”
Section: Coordinated Response Of the Time During Key Phases Of Lung Tmentioning
confidence: 99%